Effects of spent tea leaf powder on the properties and functions of cellulose green composite films. Issue 1 (March 2016) - Duan, J.; Reddy, K. Obi; Ashok, B.; Cai, J.; Zhang, L.; Rajulu, A. Varada
Highlights: Spent tea leaf has been used for the production of bio-films for the first time. Spent tea leaf reinforced cellulose films showed improved mechanical properties. The films exhibited excellent adsorption performance for methylene blue dye. A value has been added to spent tea leaf waste in the form of a filler in biodegradable polymer composite films. Abstract: The aim of the present work was to develop novel bio-based polymer composite films with improved tensile and thermal properties. In this work, cellulose and spent tea leaf powder (STLP) were used as the matrix and filler respectively in the preparation of biocomposite films. To make cellulose solution, cotton linters were dissolved in pre-cooled aqueous solution of 8 wt.% Lithium hydroxide and 15 wt.% urea. Tea is an important beverage of household and hotels and spent tea leaves form a conjugal solid waste. STLP was added to cellulose solution in 5–25 wt.% of weight of cellulose. The cellulose and cellulose/STLP composite films were prepared by regeneration method using ethyl alcohol coagulation bath. The dry films were characterized by optical microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, and tensile tests. The effect of STLP loading on the properties of the cellulose/STLP composite films was studied. The results indicated that the composite films had higher tensile properties and thermal stability than the cellulose matrix. The dye adsorption ability of cellulose and cellulose/STLP composites in wet form was also studied. It was observed that the composite wet films had higher dye adsorption capacity than the matrix. Results of this study indicated STLP to be a promising green filler for polymer matrices.